Dihydromyricetin Protects against Bone Loss in Ovariectomized Mice by Suppressing Osteoclast Activity - Zhao, Libo; Cai, Cong; Wang, Jing; Zhao, Liming; Li, Weijin; Liu, Changyu; Guan, Hanfeng; Zhu, Yuanli; Xiao, Jun (Frontiers in Pharmacology, 2017)
Dihydromyricetin (DMY), the main flavonoid component of Ampelopsis grossedentata, possesses pharmacological activities useful for treatment of diseases associated with inflammation and oxidative damage. Because osteoclasts are often involved in chronic low-grade systemic inflammation and oxidative damage, we hypothesized that DMY may be an effective treatment for osteoclast-related diseases. The effects of DMY on osteoclast formation and activity were examined in vitro. Female C57BL/6 mice were ovariectomized to mimic menopause-induced bone loss and treated with DMY, and femur samples were subjected to bone structure and histological analysis, serum biochemical indicators were also measured. DMY suppressed the activation of nuclear factor-κB, c-Fos and mitogen-activated protein kinase, and prevented production of reactive oxygen species (ROS). DMY decreased expression of osteoclast-specific genes, including Trap, Mmp-9, Cathepsin K, C-Fos, Nfatc1, and Rank. In addition, DMY prevented bone loss and decreased serum levels of tumor necrosis factor-α, interleukin-1β, and interleukin-6, and with a decrease in the ratio between receptor activator of nuclear factor-κB (RANK) ligand (RANKL) and osteoprotegerin (OPG) in vivo. These findings demonstrate that DMY attenuates bone loss and inhibits osteoclast formation and activity through modulation of multiple pathways both upstream and downstream of RANKL signaling. DMY may thus be a useful option for treatment of osteoclast-related diseases such as rheumatoid arthritis and osteoporosis.